MICROFINANCE AS A TOOL FOR ECONOMIC DEVELOPMENT IN TRANSITIONAL COUNTRIES: EXPERIENCE FROM KOSOVO - Ahmeti, Faruk (European Scientific Journal, ESJ, 2014)
Many consider microfinance as a tool for poverty decrease. Even more, especially in post-conflict countries such as Kosovo, micro-financial institutions are seen as an opportunity of reconciliation. This paper explores the implication of microfinance in Kosovo since the war ended, evaluating its effects in terms of overall poverty reduction and if microfinance institutions improved access to credit for microenterprises. Post-conflict countries such as Kosovo are the best examples where microfinance can provide its contribution on poverty reduction and better access to finance needed for startup micro-entrepreneurs. Kosovo like many states in the Balkan region has a high unemployment rate with the youngest population in Europe. Though, microfinance remains blurred for many, even for them who would benefit from this opportunity as it is not clear whether it delivers on its promises. The objective of this paper is to introduce the matter of microfinancing to a broader audience in Kosovo, to assess the economic impact of micro-financial institutions, and who has benefited the most. This paper will also introduce topics that are new and can serve as opportunities for future studies in microfinance in Kosovo.